Harmonising Tradition and Modernity: The Evolution and Cultural Significance of Dikir Barat in Singapore (Melayu: Jurnal Antarabangsa Dunia Melayu, 2025)
This paper explores the evolution and cultural significance of dikir barat in Singapore, a traditional Malay choral performance art that has become a symbol of Malay cultural identity in the region. The dikir barat, which originated from the Pattani region, is now known as a significant cultural arts practice within the Malay community in Singapore. The art form of dikir barat serves as a form of entertainment and a medium for cultural expression. Through a qualitative research approach, including in-depth interviews and video transcriptions, this study traces the historical journey of dikir barat, exploring its transformation from a traditional practice to a modern-day symbol of cultural heritage in Singapore. The research highlights dikir barat as a form of cultural capital, symbolizing the collective memory, social norms, and intrinsic values of the Singapore Malay community. This paper also examines the adaptation of the art form to contemporary contexts, incorporating modern elements while preserving its traditional essence. This adaptation has allowed dikir barat to remain relevant and appealing to younger generations, ensuring its continuity amidst the modernising society of Singapore. The findings underscore the crucial role of dikir barat in fostering cultural continuity, social cohesion, and a sense of identity within Singapore’s Malay community. The paper concludes by discussing the broader implications for cultural preservation, emphasizing the need for sustained efforts to maintain and promote dikir barat as a vibrant and integral part of Singapore’s Malay heritage, capable of resonating with both current and future generations.Full text: PDF